Cross Talk Among Calcium, Hydrogen Peroxide, and Nitric Oxide and Activation of Gene Expression Involving Calmodulins and Calcium-Dependent Protein Kinases in Ulva Compressa Exposed to Copper Excess - Moenne-Munoz, A; Morales-Munoz, B; Contreras-Arredondo, R; Gonzalez-Figueroa, A (2012)
To analyze the copper-induced cross talk among calcium, nitric oxide (NO), and hydrogen peroxide (H 2O 2) and the calciumdependent activation of gene expression, the marine alga Ulva compressa was treated with the inhibitors of calcium channels, ned-19, ryanodine, and xestospongin C, of chloroplasts and mitochondrial electron transport chains, 3-(3,4-dichlorophenyl)-1,1-dimethylurea and antimycin A, of pyruvate dehydrogenase, moniliformin, of calmodulins, N-(6-aminohexyl)-5-chloro-1-naphtalene sulfonamide, and of calcium-dependent protein kinases, staurosporine, as well as with the scavengers of NO, 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide, and of H 2O 2, ascorbate, and exposed to a sublethal concentration of copper (10 ?M) for 24 h. The level of NO increased at 2 and 12 h. The first peak was inhibited by ned-19 and 3-(2,3-dichlorophenyl)-1,1-dimethylurea and the second peak by ned-19 and antimycin A, indicating that NO synthesis is dependent on calcium release and occurs in organelles. The level of H 2O 2 increased at 2, 3, and 12 h and was inhibited by ned-19, ryanodine, xestospongin C, and moniliformin, indicating that H 2O 2 accumulation is dependent on calcium release and Krebs cycle activity. In addition, pyruvate dehydrogenase, 2-oxoxglutarate dehydrogenase, and isocitrate dehydrogenase activities of the Krebs cycle increased at 2, 3, 12, and/or 14 h, and these increases were inhibited in vitro by EGTA, a calcium chelating agent. Calcium release at 2, 3, and 12 h was inhibited by 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide and ascorbate, indicating activation by NO and H 2O 2. In addition, the level of antioxidant protein gene transcripts decreased with N-(6-aminohexyl)-5-chloro-1-naphtalene sulfonamide and staurosporine. Thus, there is a copper-induced cross talk among calcium, H 2O 2, and NO and a calcium-dependent activation of gene expression involving calmodulins and calcium-dependent protein kinases. © 2012 American Society of Plant Biologists.